Citizen Perception of Security and Visitation of Public Spaces: An Exploratory Study on Regional Public Parks in Costa Rica - Cruz Zuniga, Nidia (2023)
Through an exploratory approach, this article aimed to investigate the relationship between uses, dynamics, and perception of security from users of three urban regional parks in the metropolitan area of Costa Rica. The information was collected from direct consultation through a closed survey and a predominantly quantitative analysis. One of the main findings highlights that about 60% of surveyed people visited the parks at least once a month. They come from various neighboring cantons, but especially those hosting the parks. In addition, fear of crime influences visitation patterns, especially the hours of use. Also, aspects such as gender and age influence this perception. Finally, it is concluded that existing evidence links the perception of security and visitation patterns to this type of space. Further studies of this type are necessary to have adequate inputs for planning and designing cities, especially in Latin America.